TECHNOLOGY ACCEPTANCE MODEL AND MOBILE SHOPPING IN TURKEY: A STUDY ON CONSUMERS' INITIAL TRUST, INTENTION AND BEHAVIOR (Third Sector Social Economic Review, 2024)
The use of mobile devices has transformed the retail environment and led consumers to switch to mobile shopping. Previous studies have shown that perceived ease of use and perceived risk have an impact on trust in mobile shopping. In this study, the impact of initial trust on consumer intention and behavior is examined in depth. Mobile shopping apps involve many factors that affect consumers' shopping intentions and behaviors. Technology Acceptance Model (TAM) is frequently used to examine these factors. In this framework, initial trust in mobile shopping stands out as an important factor shaping consumers' decisions to use an application. Therefore, this study aims to examine the relationships between consumers' initial trust in mobile shopping applications, shopping intention and behavior in Turkey. The findings reveal that perceived ease of use and perceived usefulness positively affect initial trust, while perceived risk negatively affects initial trust. In addition, the study reveals that initial trust has a positive effect on mobile shopping attitude and mobile shopping attitude mediates the relationship between initial trust and mobile shopping intention. These findings provide data to help marketing professionals and firms optimize their mobile shopping strategies. Moreover, increasing initial trust is critical for strengthening consumer loyalty. Therefore, the current study revisits the importance of building initial trust in mobile applications by showing that initial trust and intention shape consumer behavior in mobile shopping applications.
Keywords: Digital Marketing; Mobile Shopping Behavior; Technology Acceptance Model; Initial Trust; Perceived Risk